2021
DOI: 10.1186/s13000-021-01137-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal seminoma with florid follicular lymphoid hyperplasia: a case report and review of the literature

Abstract: Background First described in 1955 Primary mediastinal seminomas are rare. Only 1–4% of mediastinal tumours are germ cell tumors; majority of which are teratomas. They typically present in men aged between 20 and 40 years. Very few cases are reported in the literature. Florid follicular lymphoid hyperplasia can obscure the malignant cells and is a rarer finding still. We present a rare case of a 48 year old man with a primary mediastinal seminoma with florid follicular lymphoid hyperplasia; fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies have reported misdiagnosis of PMS with thymic cyst and/or lymphoid hyperplasia and/or granulomatous in ammation [10][11][12]. These accompanying features often hide tumors and lead to missed diagnosis or misdiagnosis and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported misdiagnosis of PMS with thymic cyst and/or lymphoid hyperplasia and/or granulomatous in ammation [10][11][12]. These accompanying features often hide tumors and lead to missed diagnosis or misdiagnosis and delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…They show a sheet‐like and solid or lobular growth pattern, usually forming nests of tumour cells separated by thin fibrous septa (Figure 1A–B). There can be prominent lymphocytic infiltrates with florid lymphoid hyperplasia 81,82 or granulomatous reactions (Figure 1A) mimicking granulomatous diseases and effacing tumour cells 83,84 . Contrary to their gonadal counterpart, up to 8% of PMSEMs show cystic changes due to the induction of tumour‐associated multilocular (secondary) thymic epithelial cysts 85 .…”
Section: Primary Mediastinal Seminomamentioning
confidence: 99%
“…Despite presenting as a diagnostic challenge, PMS can present with distinct complications often related to mass effect. Known common complications of mediastinal tumors include superior vena cava (SVC) syndrome ( 8 ), chylothorax ( 9 ), pericardial effusion ( 10 ), and lymphoid hyperplasia ( 5 , 11 ). When planning for surgical removal, these tumors require remarkable precision, skill, and planning due to the nature of their location and adjacency to surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the rarity of the tumor, but also because this tumor type can be difficult to diagnose. Prior to full histologic evaluation, these tumors are often mistaken for thymic or thyroid neoplasms (3)(4)(5). For example, seminoma tumor cells have a CD117+ immunohistochemical (IHC) phenotype, a pattern also seen in thymic tumors (6).…”
Section: Introductionmentioning
confidence: 99%